1988
DOI: 10.2118/14147-pa
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Interaction of Phase Behavior With Microscopic Heterogeneity in a CO2 Flood

Abstract: This paper reports results of an experimental investigation of the effects of microscopic heterogeneity on local displacement efficiency in a CO 2 flood. Flow-visualization experiments for first-contact miscible displacements are described and compared with effluent composition measurement for the same models. High-pressure flow-visualization experiments for multicontact miscible CO 2 floods are also described. The displacements were performed in two-dimensional (2D) etched glass models made from thin-sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Numerous studies have been performed using glass micromodels. They have been used to study specific aspects related to flow in porous media such as wettability (Laroche et al, 1999;Grattoni and Dawe, 2003), capillary pressure (Smith et al, 2005), interfacial tension (Mackay et al, 1998), heterogeneity (Bahralolom et al, 1998), multiple contact miscibility (Campbell and Orr, 1985;Dastyari et al, 2005), water alternating gas injection (Sohrabi et al, 2004), solvent injection (Dehghan et al, 2010;Farzaneh et al, 2010), and gravity drainage (Chatzis et al, 1988;Bora et al, 1997;Mashayekhizadeh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed using glass micromodels. They have been used to study specific aspects related to flow in porous media such as wettability (Laroche et al, 1999;Grattoni and Dawe, 2003), capillary pressure (Smith et al, 2005), interfacial tension (Mackay et al, 1998), heterogeneity (Bahralolom et al, 1998), multiple contact miscibility (Campbell and Orr, 1985;Dastyari et al, 2005), water alternating gas injection (Sohrabi et al, 2004), solvent injection (Dehghan et al, 2010;Farzaneh et al, 2010), and gravity drainage (Chatzis et al, 1988;Bora et al, 1997;Mashayekhizadeh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Presence of water can decrease the efficiency of miscible CO 2 displacements in water wet systems as the higher saturation of wetting phase decreases the flow fraction of nonwetting phase and consequently decreases the recovery of oil in water wet systems (4) . Interaction of phase behaviour with heterogeneities leads to residual oil saturations due to preferential flow paths (5) .…”
Section: Miscible Displacementmentioning
confidence: 99%
“…In order to observe the effects of 2-D flow, Campbell and Orr (4) suggested using glass etched micro-models and visualized CO 2 /Crude oil displacements. Bahralolom et al (2,5) also used micro-models similar to the one used previously 3 . The main difference of Bahralolom's model was that pore networks on the models were etched by tracing pore patterns from an enlarged photo of thin-sections.…”
Section: Visualization Studiesmentioning
confidence: 99%
“…Gradual migration of oil from the bypassed region to the flowing region can cause the resulting composition profile to deviate from the one without the transverse mass flux (Brock and Orr, 1991;Pande and Orr, 1994a;1994b;Zhou et al, 1997). High residual oil saturations were observed in dominant flow paths due to the interaction of phase behavior with oil bypassing (Gardner and Ypma, 1984;Campbell and Orr, 1985;Bahralolom et al, 1988;Mohanty and Johnson, 1993). These results indicate the importance of considering the effects of oil bypassing on oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed in various types of experiments and field applications of gas injection. Flow-visualization experiments (Stalkup, 1970;Chatzis et al, 1983;Campbell and Orr, 1985;Bahralolom et al, 1988;Stern, 1991) showed that microscopic oil bypassing was related to pore structures with bimodal or wide pore-size distributions. Shielding of oil by water films in pores can also hinder the contact between the bypassed oil and injection gas in the region with high water saturations (Shelton and Schneider, few inches can cause marked oil bypassing by gas (McGuire et al, 1995).…”
Section: Introductionmentioning
confidence: 99%